Four Cases of Xeroderma Pigmentosum in a Pakistani Family - Arsalan, Najia Idrees, Tanveer Anjum Chaudhry (Pakistan Journal of Ophthalmology, 2014)
Xeroderma pigmentosum (XP) is a rare autosomal recessive genetic disorder resulting from the defective repair of DNA, damaged by exposure to ultraviolet radiation. This case series is focused on a Pakistani family with 4 of its members suffering from XP. An 11 year old girl belonging to this family presented to us with substantial loss of vision in right eye, intolerance to light and mild pain for the past 4 years. Her visual acuity was hand movement in the right eye and no perception of light in the left. On examination multiple hypo- and hyper pigmented areas of skin around the eyes were visible. Her signs and symptoms together with positive family history helped us reach the diagnosis of XP.